Selected Under-exploited Plant Oils in Nigeria: A Correlative Study of their Properties - Ifijen, Ikhazuagbe H.; Nkwor, Adachukwu N. (Tanzania Journal of Science, 2020)
This study examined the physicochemical properties of seven under-exploited plant oils in Nigeria, namely; Hevea brasiliensis seed oil (HBSO), Prunus dulcis seed oil (PDSO), Afzelia africana aril cap oil (AAACO), Jatropha curcas seed oil (JCSO), Sesamum indicum seed oil (SISO), Canarium schweinfurthii seed oil (CSSO) and Hura crepitans seed oil (HCSO). Characteristics such as colour, percentage yield, specific gravity, freezing/melting point, acid value, free fatty acid, iodine value, and saponification value were investigated. The results showed that they have different colours and are liquid at room temperature. The percentage yield of the extracted oils varied from 34 to 55.39%. The specific gravities which were observed to agree with what is obtainable in most vegetable oils were in the range of 0.91 in PDSO to 0.948 in CSSO. The freezing/melting points show that CSSO (8.89 °C), AAACO (6.39 ºC) and JCSO (3.18 ºC) have greater amounts of saturated fatty acids than SISO (–6.21 ºC), HCSO (–15.34 ºC) and HBSO /PDSO (–18 ºC). The acid values and free fatty acids of the oils were in the range of 2.13–17.49 mg KOH/g and 1.07–9.648%, respectively. The iodine values of HBSO, PDSO, JCSO, and SISO (104–128.9 mg iodine/100 g) and AAACO and CSSO (68–77 mg iodine/100 g) placed them in the semi-drying and non-drying class, respectively. Their saponification values (137.2 to 210 mg KOH/g oil) suggest their possible applications in the soap industry. The results generally present a deductive justification for the usage of the studied plant seed oils for some industrial and other applications.